Mainstreaming Law and Human Rights Education in Indonesia: How the National Training Institute Can Drive Legal and Policy Reform? - Kurniawan, Iwan; Pramono, Suwito Eko; Yulianto, Arief; Formen, Ali (Journal of Law and Legal Reform, 2024)
This paper explores the integration of law and human rights education in Indonesia, with a focus on the role of the National Training Institute (NTI) in advancing these principles through governmental and public service training programs. As Indonesia continues its commitment to upholding human rights, both domestically and in line with international conventions, the mainstreaming of law and human rights education plays a critical role in promoting justice, equality, and legal literacy across society. Despite legal frameworks aimed at protecting human rights, there remains a significant gap in the effective implementation of such education, particularly within public institutions and civil service training. The study assesses how the NTI has integrated law and human rights topics into its curricula, examining the effectiveness of these programs in building awareness and understanding of legal rights and responsibilities. Drawing from interviews with trainers and participants, the paper identifies both strengths and limitations of current training methodologies, highlighting the challenges of addressing complex human rights issues in a culturally diverse context. Furthermore, the research underscores the importance of law and policy reform in advancing human rights education. It argues that a comprehensive and systematic approach to training in legal rights is not only crucial for improving compliance with national and international human rights standards but is also integral to broader legal reforms aimed at enhancing public participation and accountability in governance. The paper concludes by proposing recommendations for strengthening law and human rights education within the NTI framework, advocating for reforms that expand its reach and effectiveness as a tool for both societal change and legal empowerment.